Symbolic immersion ceremony - Mumbai Archive Project Team (Jio Institute, 2024)
The boats head for the sea, where a symbolic immersion ceremony is held. The facemask is removed and dipped in the sea three times, while the coconuts are offered to the sea along with flowers and other items used in the puja (prayers of devotional homage) ceremony.